Relationship Raisin Between 60% Extract Solution And Saliva pH - Benni Benyamin; Endah Aryati Ekoningtyas; Sulur Joyo Sukendro (Jurnal Kesehatan Gigi, 2022)
Caries is a dental and oral disease with the highest percentage. One of the groups that are susceptible to caries is children. Caries is a dental and oral disease that has several causative factors, including the acid-base state of the oral cavity and also the status of oral hygiene. Prevention of caries can be done by controlling the pH of saliva by gargling a solution of raisins containing flavonoids, tannins, and triterpenoids which can control salivary pH. The purpose of this study was to determine the relationship between gargling 60% raisin solution on salivary pH in children aged 13-16 years. This type of research is analytic research, namely true experimental research. The sample consisted of 32 children, consisting of the intervention group (gargling with 60% raisin solution) and the control group (gargling with distilled water). Data analysis was performed using a dummy independent variable linear regression test. The results of statistical tests showed that there was a relationship between gargling 60% raisin solution on the pH of saliva with a unidirectional relationship and the strength of the relationship was sufficient with the R coefficient value of salivary pH = 0.384. Further research is needed on the effect or relationship of raisin varieties or other types on salivary pH with different target characteristics, as well as the manufacture of mouthwash preparations made from raisins.